Obinutuzumab, acalabrutinib, and venetoclax, after an optional debulking with bendamustine in relapsed or refractory chronic lymphocytic leukaemia (CLL2-BAAG): a multicentre, open-label, phase 2 trial - Cramer, Paula; Fürstenau, Moritz; Robrecht, Sandra; Giza, Adam; Zhang, Can; Fink, Anna-Maria; Fischer, Kirsten; Langerbeins, Petra; Al-Sawaf, Othman; Tausch, Eugen; Schneider, Christof; Schetelig, Johannes; et al. (The lancet. Haematology, 2022)
Background - Although BTK inhibitors provide long-term disease-control in patients with chronic lymphocytic leukaemia, they need to be combined with BCL2 inhibitors or antibodies to achieve deep responses with undetectable minimal residual disease (uMRD), which allows for time-limited treatment. This trial aims to evaluate the triple combination of obinutuzumab, acalabrutinib, and venetoclax after an optional debulking with bendamustine. - Methods - This multicentre, open-label, investigator-initiated, phase 2 study evaluates a sequential treatment consisting of a debulking with two cycles of bendamustine for patients with a higher tumour load (70 mg/m2 intravenously on days 1 and 2, repeated after 28 days), followed by an induction and a maintenance with obinutuzumab (1000 mg intravenously on days 1-2, 8, and 15 of the first induction cycle, every 4 weeks in induction cycles 2-6 and every 12 weeks in the maintenance phase), acalabrutinib (100 mg orally twice daily continuously from induction cycle 2 day 1 onwards) and venetoclax (starting in induction cycle 3 with 20 mg per day with a weekly dose ramp-up over 5 weeks to the target dose of 400 mg per day). Eligible patients were aged 18 years or older with an ECOG performance score 0-2 and had relapsed or refractory chronic lymphocytic leukaemia requiring treatment according to the 2018 International Workshop on Chronic Lymphocytic Leukemia criteria. The primary endpoint was uMRD (<10−4) in peripheral blood at the end of induction treatment assessed centrally at the final restaging, 12 weeks after the start of the last induction cycle. As per protocol, all patients with more than two induction cycles were included in the analyses. This study is registered with ClinicalTrials.gov, number NCT03787264, and is ongoing. - Findings - Between Jan 14, 2019, and June 25, 2020, 45 evaluable patients with relapsed or refractory chronic lymphocytic leukaemia were enrolled; 13 (29%) were female, 32 (71%) were male, 21 (47%) had already received a targeted agent, and 14 (32%) had del(17)(p13.1) or TP53 mutation. Ethnicity-race data was not collected. At data cutoff (Feb 25, 2021), all patients had completed the induction treatment. 34 patients (76%; 95% CI 61-87, p=0·26) had uMRD in peripheral blood after 6 months of triple therapy. Until data cutoff, 32 (71%) patients started maintenance and nine (28%) were able to stop with uMRD. After a median observation time of 13·8 months (IQR 10·4-18·4), there were two (4%) Richter transformations, but no progressions and no deaths observed. The most common adverse events of grade 3 and 4 during the entire treatment were thrombocytopenia and neutropenia (12 [27%] of 45 patients each), tumour lysis syndrome and infections (five [11%] of 45 patients each, grade 3 adverse events only), infusion-associated reactions (four [9%] of 45 patients) and anaemia (four [9%] of 45 patients). - Interpretation - With 76% of patients achieving uMRD in peripheral blood, this trial did not reach the prespecified activity threshold. Triple therapy with obinutuzumab, acalabrutinib, and venetoclax after an optional debulking with bendamustine regimen requires further evaluation in larger trials to define its value compared with double treatment with a BTK or BCL2 inhibitor combined with obinutuzumab or a combination of the two oral targeted drugs. Until these trials show a clear benefit, the use of the triple combination in routine practice cannot be recommended. - Funding - Acerta, AstraZeneca, F Hoffmann-La Roche, and AbbVie.
Gesehen am 23.01.2023